Determinan Factors of Sustainability Report : The Moderating Role of Institutional Ownership - Sabrina Gesila Finca; Agus Ismaya Hasanudin; Nurhayati Soleha (Cita konsultindo, 2025)
This study examines the influence of corporate governance mechanisms (board size and board independence) and profitability on the quality of sustainability report, with institutional ownership as a moderating variable in non-cyclical consumer companies listed on the Indonesia Stock Exchange during 2020-2023. Using quantitative analysis of 96 observations through Moderated Regression Analysis, the results reveal that board size and board independence have a positive effect on sustainability report, while profitability does not show a significant effect. Furthermore, institutional ownership moderates by weakening the relationship between governance mechanisms and sustainability report, but does not moderate the relationship between profitability and sustainability report.